Design and synthesis of aminoester heterodimers containing flavone or chromone moieties as modulators of P-glycoprotein-based multidrug resistance (MDR). Issue 1 (1st January 2018) - Dei, Silvia; Romanelli, Maria Novella; Manetti, Dina; Chiaramonte, Niccolò; Coronnello, Marcella; Salerno, Milena; Teodori, Elisabetta
Graphical abstract: Highlights: New N, N - bis(alkanol)amine- and N, N - bis(ethoxyethanol)amine aryl esters were obtained. They carry a methoxylated aryl residue combined with a flavone or chromone moiety. These heterodimers were evaluated for their P-gp-dependent MDR modulating activity. This new series of compounds does not comply with the SAR previously outlined. The characteristics of the spacer seem to be critical for the interaction with P-gp. Abstract: In this study, a new series of heterodimers was synthesized. These derivatives are N, N - bis(alkanol)amine aryl esters or N, N - bis(ethoxyethanol)amine aryl esters carrying a methoxylated aryl residue combined with a flavone or chromone moiety. The new compounds were studied to evaluate their P-gp modulating activity on a multidrug-resistant leukemia cell line. Some of the new compounds show a good MDR reversing activity; interestingly this new series of compounds does not comply with the structure-activity relationships (SAR) outlined by previously synthesized analogs carrying different aromatic moieties. In the case of the compounds described in this paper, activity is linked to different features, in particular the characteristics of the spacer, which seem to be critical for the interaction with the pump. This fact indicates that the presence of a flavone or chromone residue influences the SAR of these series of products, and that flexible molecules can find different productive binding modes with the P-gp recognition site. These results support the synthesis of new compounds that might be useful leads for the development of drugs to control P-gp-dependent MDR.